A degree 5 polynomial P ( x ) has the property that the remainder when P ( x ) is divided by ( x − a ) is a for a = 1 → 5 . If P ( 0 ) = − 1 , find the value of P ( 1 2 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I like your references. :D
I'm a bit confused. If P ( x ) = 1 2 0 1 ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) + x , when P ( x ) is divided by x − 1 the remainder is x not 1 ?
Log in to reply
Note that dividing by a linear polynomial cannot yield a linear remainder. You can see that you can reduce the remainder further: x − ( x − 1 ) = 1 so we get a remainder of 1 .
As a general rule of thumb, we can express P ( x ) = D ( x ) Q ( x ) + R ( x ) , and deg ( R ( x ) ) < deg ( D ( x ) ) .
basic toughness!
I did it with linear equations in 6 variables ...... So easy
I THOUGHT OF EXACTLY THIS!!! but I got confused with how to find 'c'! So I went on the long 5 var path...
i did it exactly the same way...its easy....
From Remainder-Factor Theorem we have P ( a ) = a , for a = 1 , 2 , 3 , 4 , 5 .
⇒ P ( x ) = x , for x = 1 , 2 , 3 , 4 , 5 .
Since P ( x ) is a degree 5 polynomial, so we let P ( x ) − x = A ⋅ ( x − 1 ) ⋅ ( x − 2 ) ⋅ ( x − 3 ) ⋅ ( x − 4 ) ⋅ ( x − 5 ) , for some A = 0 .
From given conditions i.e. P ( 0 ) = − 1 we have
− 1 − 0 = A ⋅ ( − 1 ) ⋅ ( − 2 ) ⋅ ( − 3 ) ⋅ ( − 4 ) ⋅ ( − 5 )
⇒ A = 1 ⋅ 2 ⋅ 3 ⋅ 4 ⋅ 5 1
Now P ( 1 2 ) = 1 2 + A ⋅ ( 1 2 − 1 ) ⋅ ( 1 2 − 2 ) ⋅ ( 1 2 − 3 ) ⋅ ( 1 2 − 4 ) ⋅ ( 1 2 − 5 )
⇒ P ( 1 2 ) = 4 7 4 .
wow
I recently learned how to solve problems like these, so here goes:
From the remainder theorem, we know that P ( a ) = a for a = 1 , 2 , 3 , 4 , 5 . Let us define a new function Q ( x ) = P ( x ) − x . Now, we know that x − a is a factor of Q ( x ) for a = 1 , 2 , 3 , 4 , 5 . Note that Q ( x ) is also a degree 5 polynomial. Hence:
Q ( x ) = P ( x ) − x = a ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) , where a is some arbitrary constant.
But we know that P ( 0 ) = − 1 . Substituting this into the above function:
⟹ P ( 0 ) − 0 = a ( 0 − 1 ) ( 0 − 2 ) ( 0 − 3 ) ( 0 − 4 ) ( 0 − 5 )
⟹ − 1 = a ( − 1 ) ( − 2 ) ( − 3 ) ( − 4 ) ( − 5 )
⟹ a = 1 2 0 1
Hence, Q ( x ) = 1 2 0 1 ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) , which means that P ( x ) = 1 2 0 1 ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) + x .
Substituting x = 1 2 into the function, we get:
⟹ P ( 1 2 ) = 1 2 0 1 ( 1 2 − 1 ) ( 1 2 − 2 ) ( 1 2 − 3 ) ( 1 2 − 4 ) ( 1 2 − 5 ) + 1 2
⟹ P ( 1 2 ) = 4 7 4
The given polynomial can be written as
P ( x ) = k ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) + x
where k is a constant.
The remainder when P ( x ) is divided by ( x − a ) is P ( a ) which holds true for 1 to 5 according to the given statement.
Since P ( 0 ) is − 1 , we get P ( 0 ) = k ( − 1 ) ( − 2 ) ( − 3 ) ( − 4 ) ( − 5 ) = − 1 ⟹ k = 5 ! 1 .
Thus, we get P ( 1 2 ) = 4 7 4
By the Factor Theorem , we have:
P ( x ) − x = n ( a = 1 ∏ 5 ( x − a ) )
Here n is a constant. Since we have P ( 0 ) = − 1 , plugging in x = 0 , we have:
P ( 0 ) − 0 = n ( a = 1 ∏ 5 − a ) ⟹ − 1 = n ⋅ ( − 1 2 0 ) ⟹ n = 1 2 0 1
∴ P ( x ) = x + 1 2 0 1 ( a = 1 ∏ 5 ( x − a ) )
Plugging in x = 1 2 , we get our desired result:
P ( 1 2 ) = 1 2 + 1 2 0 1 ( a = 1 ∏ 5 ( 1 2 − a ) ) = 1 2 + 1 2 0 1 1 × 1 0 × 9 × 8 × 7 = 1 2 + 4 6 2 = 4 7 4
consider..... g ( x ) = P ( x ) − x . then for x = 1 → 5 g ( x ) = K ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) where K is a constant
Given P ( 0 ) = − 1 we put x=0 ⇒ c ( − 1 ) ( − 2 ) ( − 3 ) ( − 4 ) ( − 5 ) = − 1 ⇒ c = 1 2 0 1 P ( x ) = g ( x ) + x = x + 1 2 0 1 ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) P u t x = 1 2 . . . w e g e t P ( x ) = 4 7 4
I did it the long way. There should be a better way. Solution: constant term = -1 use 5 eq and 5 variables to find the equation P(x) then find P(6)=474
This is basically an application of remainder Theorem and linear equation solution. You need to know the theorem that when f(x) is divided by (x-a), the remainder is always f(a). Thus we get the following linear equtions f(0)=-1; f(1)=1; f(2)=2; f(3)=3; f(4)=4; f(5)=5; Observe that these equations are linear with the coefficients being the unknowns. Now all you need to know is how to solve a linear equation of type Ax=b. the solution is inverse(A).b there . is the usual matrix multiplication.
P.S. I don't have enough patience to invert a 5*5 matrix, so I wrote i small piece of R-code for everything. Here is the code:
A=matrix(1,5,5); for(i in 1 :5) { A[i,]=i^c(1:5) }; a=c(2:6); beta=ginv(A)% %a; beta=c(-1,beta); ans=sum(12^c(0:5) beta); print(ans); This app has some problem with newlines. place a newline at every ";".
By the remainder theorem we have P ( a ) = a , so we define Q ( x ) = P ( x ) − x , consequently Q ( x ) has roots at 1 , 2 , 3 , 4 , 5 and we can write it as
Q ( x ) = ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) C ⟶ P ( x ) = ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) C + x Plugging in 0 we can evalute C , so
P ( 0 ) = − 1 = − 5 ! C ⟶ C = 1 2 0 1
Finally
P ( 1 2 ) = 1 1 ⋅ 1 0 ⋅ 9 ⋅ 8 ⋅ 7 ⋅ 1 2 0 1 + 1 2 = 4 7 4 .
Since P(x), when divided by (x-a) gives P(a) as the result, P(1)=1, P(2)=2, P(3)=3, etc. and P(0)=-1. Using these points, one can create a 6x7 matrix. Then use rref (reduced-row-echelon-form) on the matrix to get the coefficient values of the 5th degree polynomial and then plug in 12 into the resultant polynomial.
Let P ( x ) − x = Q ( x ) for some polynomial Q ( x ) . Since P ( x ) is of degree 5, so is Q ( x ) . Note that Q ( x ) has roots 1 , 2 , 3 , 4 , 5 , so we can write Q ( x ) = c ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) . We are also given that P ( 0 ) = − 1 ⟹ − 1 2 0 c = − 1 ⟹ c = 1 2 0 1 .
Finally, plugging in 12 gives P ( 1 2 ) − 1 2 = 1 2 0 1 ( 1 1 ) ( 1 0 ) ( 9 ) ( 8 ) ( 7 ) ⟹ P ( 1 2 ) = 4 7 4 .
We can easily see that P ( x ) − x has roots 1 , 2 , 3 , 4 , 5 . Since P ( x ) − x is also a quintic polynomial, we have that P ( x ) − x = a ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) for some real a . Substituting ( 0 , − 1 ) gives us P ( 0 ) = a ( − 1 ) ( − 2 ) ( − 3 ) ( − 4 ) ( − 5 ) = − 1 ⟹ a = 1 2 0 1 So P ( 1 2 ) − 1 2 = 1 2 0 1 ( 1 1 ) ( 1 0 ) ( 9 ) ( 8 ) ( 7 ) = 4 6 2 ⟹ P ( 1 2 ) = 4 7 4 .
Problem Loading...
Note Loading...
Set Loading...
First, notice that d e g ( P ( x ) − x ) = 5 . Since P ( x ) − x = 0 for x = 1 , 2 , 3 , 4 , 5 , it follows that P ( x ) − x = c ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) for some constant c .
Since we are given P ( 0 ) = − 1 , we can try plugging 0 in: P ( 0 ) − 0 = c ( − 1 ) ( − 2 ) ( − 3 ) ( − 4 ) ( − 5 ) = − 1 ⇒ c = 1 2 0 1 .
Therefore, we have P ( x ) − x = 1 2 0 1 ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) .
Now, plugging in x = 1 2 , we have P ( 1 2 ) − 1 2 = 1 2 0 1 1 ⋅ 1 0 ⋅ 9 ⋅ 8 ⋅ 7 = 1 1 ⋅ 7 ⋅ 6 = 4 6 2 . It follows that P ( 1 2 ) = 4 6 2 + 1 2 = 4 7 4 *
*This can be computed in many different ways. See http://faculty.atu.edu/mfinan/2033/section12.pdf